An evaluation study of the climate change adaptation plans for a provincial conservation authority in South Africa - Van den Berg-McGregor, Eleanor Charmell (Rhodes University, Faculty of Commerce, Rhodes Business School)
While there are natural changes in climate over time, the climate change phenomenon of global warming that the Earth is currently experiencing is human-induced. The impact of human-induced climate change has led to unprecedented global warming and has become evident as there have been increases in the frequency and intensity of extreme weather events such as inter alia, heatwaves, droughts and floods. This climate change trajectory poses a risk to the Earth's ability to continue providing sustainable ecosystem services necessary to sustain life on Earth. Therefore, considering the risks and impacts of climate change, there is a need to strengthen the global response to the threat of climate change, and hence, there is a need for climate change adaptation (CCA). Some benefits of CCA include the reduction of risks to nature and people, biodiversity conservation, food security, livelihoods and human well-being. Through a CCA lens within the biodiversity and conservation sector, underpinned by Resilience Theory, this research study sets out to identify and evaluate the CCA plans of a provincial conservation authority. By reviewing the current literature for CCA, the insights gained allowed for the emergence of key characteristics for good CCA in the biodiversity and conservation sector, and the evaluation of CapeNature's (a provincial conservation authority situated in the Westen Cape of South Africa) CCA plans against these key characteristics that emerged for CCA and resilience planning in protected areas and ecosystems. Qualitative data was gathered via focus groups and individual semi-structured interviews with seven key knowledge holders of CapeNature's CCA planning processes, plans and management approaches, and through document analysis of the entity's CCA plans, whereafter it was evaluated against the key characteristics. Challenges towards CCA and opportunities that can be explored for CCA were identified as well. This research study has revealed that CapeNature does not have a single all-encompassing CCA plan but has various CCA approaches that consider the key characteristics necessary for good CCA. However, the entity faces various challenges regarding its intention to implement these approaches over the long term. Challenges ranged from a fragmented approach to CCA to compromised capacity and capability to implement their CCA plans over time. A recurring challenge was the lack of financial resources, and this, combined with the entity's current inability to secure sustainable financing, was emphasised as the key factor to be addressed towards facilitating the success of the entity's CCA plans. It also emerged that CCA approaches are interdependent and linked as in various instances, when one key CCA characteristic was compromised, it had a detrimental effect on other CCA approaches. The study concludes by making recommendations to enhance CapeNature's CCA and resilience planning, noting that these may be of relevance to other conservation agencies as well.
Keywords: Climate change adaptation; Climatic changes -- South Africa; Ecosystem-based adaptation; Resilience (Ecology); Protected areas -- South Africa